2002
DOI: 10.1590/s0100-204x2002000500018
|View full text |Cite
|
Sign up to set email alerts
|

Início de florescimento, produção e valor nutritivo de gramíneas forrageiras tropicais sob condição de sombreamento natural

Abstract: Um experimento foi conduzido para estudar seis gramíneas forrageiras tropicais quanto ao seu valor nutritivo, florescimento, e produção de matéria seca quando sombreadas por árvores de angico-vermelho (Anadenanthera macrocarpa). Foram estudadas as gramíneas Brachiaria brizantha cv. Marandu, Panicum maximum cvs. Aruana, Makueni, Mombaça e Tanzânia e Cynodon dactylon cv. Tifton 68. O desempenho das gramíneas sob as árvores foi comparado com o obtido em área próxima, sem árvores (controle). O sombreamento retardo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
10

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
1
13
0
10
Order By: Relevance
“…Cecato et al (2000) reported a smaller leaf dry mass yield and total dry mass (stalks+leaves) of Aruana grass (despite greater tillering), when compared to cultivars Centenário, Mombaça, Tanzânia, and Tobiatã, and to P. maximum accessions K249 and KK8. Carvalho et al (2002) also reported smaller dry mass yield of Aruana grass tops in relation to cultivars Makueni, Mombaça, and Tanzânia. However, an observation must be made that the smaller yields presented by Aruana grass should not be attributed to less soil fertility requirements, but possibly to the same management adopted for cultivars with distinct morphogenetic characteristics.…”
Section: Introductionmentioning
confidence: 81%
“…Cecato et al (2000) reported a smaller leaf dry mass yield and total dry mass (stalks+leaves) of Aruana grass (despite greater tillering), when compared to cultivars Centenário, Mombaça, Tanzânia, and Tobiatã, and to P. maximum accessions K249 and KK8. Carvalho et al (2002) also reported smaller dry mass yield of Aruana grass tops in relation to cultivars Makueni, Mombaça, and Tanzânia. However, an observation must be made that the smaller yields presented by Aruana grass should not be attributed to less soil fertility requirements, but possibly to the same management adopted for cultivars with distinct morphogenetic characteristics.…”
Section: Introductionmentioning
confidence: 81%
“…No consórcio, o capim Tifton 85 apresentou produção de MS inferior, devido à sua baixa tolerância ao sombreamento. CARVALHO et al (2002), ao estudarem os capins Tifton 68 e B. brizantha, constataram a intolerância do Tifton 68 ao sombreamento por meio da redução na produção de MS, enquanto a B. brizantha apresentou tolerância moderada. Em monocultivo ou consorciado com as gramíneas, o feijão-guandu apresentou produção de MS semelhante, porém, com o passar dos cortes, observou-se uma redução na produção de MS, devido ao envelhecimento da forrageira, classificada como perene de vida curta (DEMINICIS, 2009).…”
Section: -----------------------Ama (Cm) ----------------------------unclassified
“…The monoculture system had the greatest TDM production, which was higher than the intercropping system regardless of height. The lower production rates in the intercropping system, according to Carvalho et al (2002), are related to the influence of shading on the grass, which changes the incidence of solar radiation in the understory, as well as the tree distribution and competition for water and nutrients between the tree component and the grass (PACIULLO et al, 2011). The modification of the photosynthetically active radiation by shading affects the photosynthetic pathway and translocation of photoassimilates of tropical grasses that display the C 4 photosynthetic pathway (DIAS-FILHO, 2000), which is the main limiting factor to pasture productivity in intercropping with trees in shading level adopted that could compromise forage growth (BELESKY, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This was due to the grass development speed in the shading system being slower, thus modifying the tiller senescence time, which is affected by factors such as shading level, intercepted brightness level, relative humidity and high content of soil moisture (CASTRO et al, 1999). Shading slows the reproductive stage of the grass, which may be related to the higher vegetative stage time in this particular environment imposed by the woods (CARVALHO et al, 2002).…”
Section: Resultsmentioning
confidence: 99%